Ultrafine IrNi Bimetals Encapsulated in Zeolitic Imidazolate Frameworks‐Derived Porous N‐Doped Carbon for Boosting Oxygen Evolution in Both Alkaline and Acidic Electrolytes. Issue 24 (16th November 2020) - Chen, Xiu; Xu, Mingyue; Li, Shang; Li, Cuicui; Sun, Xuechu; Mu, Shichun; Yu, Jun
Abstract: Developing cost‐effective and active catalysts for oxygen evolution reaction (OER) towards renewable energy‐related system, and applying the catalysts under both alkaline and acidic conditions is still a great challenge. In this work, a facile wet‐chemical method is reported to synthesize ultrafine Irx Niy alloy encapsulated in porous N‐doped carbon (BMNC) derived from bimetallic zeolitic imidazolate frameworks (ZIFs). Benefiting from the advantages of alloy effect between Ir and Ni, high surface area and more active site exposing, the optimal sample Ir3 Ni2 /BMNC with only 7.7 wt% Ir content reveals outstanding OER electrocatalytic activity in alkaline and acidic electrolyte. When evaluated in 1 m KOH, Ir3 Ni2 /BMNC exhibits low overpotential of 279 mV to drive current density of 10 mA cm −2 compared with IrO2 (322 mV), 59.4 times Ir mass activity of 303 A gIr −1 higher than IrO2 (5.1 AgIr −1 ) and prominent durability of 40 000 s for chronopotentiometry test. Assessed in 0.1 m HClO4, Ir3 Ni2 /BMNC also possesses long stability of 40 000 s for chronopotentiometry, high current density (η10 = 321 mV) and 19.9 times Ir mass activity (303 A gIr −1 ) superior to IrO2 of η10 = 350 mV and 15.2 A gIr −1, respectively. The brilliant durability attributes to the structure of alloy nanoparticles anchored in porous N‐doped carbon. Abstract : Ultrafine Irx Niy alloy is encapsulated in porous N‐doped carbon (BMNC) derived from bimetallic Zn‐Co‐ZIFs. The optimal sample Ir3 Ni2 /BMNC with only 7.7 wt% Ir content exhibits high current density in 1 m KOH (η10 = 279 mV) and 0.1 m HClO4 (η10 = 321 mV) owing to effect between Ir and Ni, high surface area, and more active site exposing.